The Chemosensitizing Role of Metformin in Anti-Cancer Therapy - Tang, Zhimin; Tang, Nan; Jiang, Shanshan; Bai, Yangjinming; Guan, Chenxi; Zhang, Wansi; Fan, Shipan; Huang, Yonghong; Lin, Hui; Ying, Ying (Anti-cancer agents in medicinal chemistry, 2021)
Chemoresistance, which leads to the failure of chemotherapy and further tumor recurrence, presents the largest hurdle for the success of anti-cancer therapy. In recent years, metformin, a widely used first-line antidiabetic drug, has attracted increasing attention for its anti-cancer effects. A growing body of evidence indicates that metformin can sensitize tumor responses to different chemotherapeutic drugs, such as hormone modulating drugs, anti-metabolite drugs, antibiotics, and DNA-damaging drugs via selective targeting of Cancer Stem Cells (CSCs), improving the hypoxic microenvironment, and by suppressing tumor metastasis and inflammation. In addition, metformin may regulate metabolic programming, induce apoptosis, reverse Epithelial to Mesenchymal Transition (EMT), and Multidrug Resistance (MDR). In this review, we summarize the chemosensitization effects of metformin and focus primarily on its molecular mechanisms in enhancing the sensitivity of multiple chemotherapeutic drugs, through targeting of mTOR, ERK/P70S6K, NF-κB/HIF-1 α, and Mitogen- Activated Protein Kinase (MAPK) signaling pathways, as well as by down-regulating the expression of CSC genes and Pyruvate Kinase isoenzyme M2 (PKM2). Through a comprehensive understanding of the molecular mechanisms of chemosensitization provided in this review, the rationale for the use of metformin in clinical combination medications can be more systematically and thoroughly explored for wider adoption against numerous cancer types.>.